Foreign Banks and the Vienna Initiative : Turning Sinners Into Saints? - De Haas, Ralph (IMF Working Papers; Working Paper ;, 2012)
We use data on 1,294 banks in Central and Eastern Europe to analyze how bank ownership and creditor coordination in the form of the Vienna Initiative affected credit growth during the 2008-09 crisis. As part of the Vienna Initiative western European banks signed country-specific commitment letters in which they pledged to maintain exposures and to support their subsidiaries in Central and Eastern Europe. We show that both domestic and foreign banks sharply curtailed credit during the crisis, but that foreign banks that participated in the Vienna Initiative were relatively stable lenders. We find no evidence of negative spillovers from countries where banks signed commitment letters to countries where they did not.